A guide to biblical Hebrew syntax - Arnold, Bill T.; Choi, John H. (2018)
"A Guide to Biblical Hebrew Syntax introduces and abridges the syntactical features of the original language of the Hebrew Bible/Old Testament. An intermediate-level reference grammar for Biblical Hebrew, it assumes an understanding of elementary phonology and morphology, and it defines and illustrates the fundamental syntactical features of Biblical Hebrew that most intermediate-level readers struggle to master. The volume divides Biblical Hebrew syntax and morphology, into four parts. The first three cover the individual words (nouns, verbs, and particles) with the goal of helping the reader move from morphological and syntactical observations to meaning and significance"--
Includes bibliographical references (pages 221-233) and index.
Keywords: Bible. -- Language, style; Hebrew language -- Syntax